Perilaku Altruisme Kelompok Masyarakat Peduli Pemasyarakatan dalam Program Bimbingan Karir Bagi Mantan Narapidana di Balai Pemasyarakatan Purwokerto - Syaiful Arifin; Mela Siti Fadilah; Kholil Lur Rochman (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study discusses the role of altruistic behavior in supporting career guidance programs for former prisoners at the Purwokerto Correctional Center. Former prisoners often face challenges in social reintegration, especially due to societal stigma and limited access to employment. Altruism-based career guidance programs aim to equip them with skills and psychosocial support to increase employment opportunities and economic independence. This study uses a qualitative approach with in-depth interviews, observations, and document analysis methods. The results show that the role of volunteers and communities with social concerns is very important in reducing barriers to the reintegration of former prisoners. The support provided is not only in the form of job skills training, but also in psychosocial assistance that helps increase their motivation and self-confidence. Although this program has a positive impact, there are still various challenges such as limited funding, lack of community participation, and strong social stigma. Therefore, collaborative efforts are needed between the government, social organizations, and the community to create a more inclusive environment for former prisoners.